2005
DOI: 10.1111/j.1365-2842.2005.01464.x
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive bonding of a lithium disilicate ceramic material with resin‐based luting agents

Abstract: This study evaluates the bonding characteristics of a lithium disilicate-based ceramic material (IPS Empress 2). Two sizes of disk specimens of the material were made, and three groups of disk pairs were separately surface-prepared using three techniques; etching with phosphoric acid, etching with hydrofluoric acid, and air-abrasion with alumina. Each group was further divided into four sub-groups; group (i) was bonded with the Variolink II composite, (ii) was treated with the Monobond-S silane primer and bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
1
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 20 publications
3
73
1
8
Order By: Relevance
“…While some authors found no significant effect on adhesion [31,32], others did [33,34]. Its effect on bond strength is contradictory and seems to depend on the number of cycles [35,36], size of the specimens [36,37] and the C-factor [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…While some authors found no significant effect on adhesion [31,32], others did [33,34]. Its effect on bond strength is contradictory and seems to depend on the number of cycles [35,36], size of the specimens [36,37] and the C-factor [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Durable adhesion between dental tissues and ceramics plays a crucial role in the success of restorations that do not have retentive properties [2][3][4][5][6]. When bonding ceramic restorations to dental substrates, it is crucial to ensure optimal adhesion of resin cement to both the dentin and ceramic surface [7][8][9]. Thus, the integrity of dentin-cement and cement-ceramic interface is essential for the survival of bonded restorations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Además de ser una alternativa reciente de gran disponibilidad en nuestro medio, presenta un costo moderado. El material ofrece una resistencia de 400±40 MPa y, por medio del acondicionamiento con ácido fluorhídrico y silano, es posible la adhesión a su restauración definitiva lo que podría aumentar su resistencia (Nagai et al, 2005;Ivoclar Vivadent, 2008;Fischer et al, 2008).…”
Section: Introductionunclassified